Technical report: heat transfer effect on MHD boundary layer flow over a non-linear shrinking sheet / Mohd Syafiqul Syamil Mohd Sofian, Mohd Hakimi Itam and Muhd Faezie Mohd Sabry - Mohd Sofian, Mohd Syafiqul Syamil; Itam, Mohd Hakimi; Mohd Sabry, Muhd Faezie (2016)
Over the years, the demands for studies of boundary layer flow has been increasing significantly as there are many practical industrial applications in engineering processes can get major benefits from the research since the quality of products such as copper wire and papers are depending on the heat transfer and flow field. This study is focusing on the effect of heat transfer on the flow of MHD boundary layer on a non-linear stretching or shrinking sheet. This project analyze the MHD fluid's boundary layer flow on a shrinking sheet and study the effects of Prandtl numbers, magnetic parameter and velocity exponential parameter on the temperature and velocity profile. The non-linear ordinary equations will be solved using Maple 18. The results obtained show that the thermal boundary layer decreases as the Prandtl numbers, magnetic parameter and velocity exponential parameter increase. The fluid velocity profiles increases when higher magnetic parameter or velocity exponential parameter increased. The fluid velocity profiles is not affected by Prandtl numbers.